Practical work in science education: a systematic literature review - Oliveira, Hugo; Bonito, Jorge (Frontiers in Education, 2023)
Practical work has taken a leading role in science teaching, particularly since the 1960s. 16 Its goals are mainly oriented towards the development of sensitivity and taste for the 17 study of physical and natural phenomena, bringing students closer to the daily reality 18 experienced by researchers working in these areas of knowledge, while promoting 19 educational success. However, these purposes have not always been achieved so, over 20 time, limitations to the way that practical work has been developed have also been 21 identified. In order to recognize the current state of the art on the development of the 22 practical work in the teaching of sciences, a systematic literature review was designed, 23 especially focused on the definition of the concept of practical work, its advantages, 24 evaluation methodologies, and the criticism/limitations attributed to its implementation. 25 To this end, four databases and one aggregator were used, to identify 53 international 26 scientific publications. Analysis of this corpus allowed the identification of 8 categories 27 associated to the concept of practical work, 5 categories associated to its advantages, 6 28 categories with the types/methodologies of evaluation and 5 categories associated with 29 the limitations of this methodology. (From this analysis) it is concluded that most 30 authors considers that the main idea integrative idea of the concept of practical work 31 should be the manipulation of materials in practical activities (hands-on style), and the 32 main advantage of this methodology comes from the fusion between the development of 33 practical skills and the conceptual understanding (minds-on). In the evaluation methods, 34 the context, procedures and specific instruments are favored and the main limitation 35 pointed to this methodology is that the way practical work is implemented, is often not 36 in agreement with the methods and techniques used by scientists and researchers.